G.H.A Juynboll and his methodology in dealing with prophetic tradition: a re-appraisal - Mohd Mokhtar, Asmilyia; Mohd Noor, Ahmad Yunus; Abd Rahman, Zaizul (IAEME Publication, 2018)
G.H.A Juynboll is considered as one of the prominent western thinkers and scholars in contemporary Orientalists world. He has produced a numerous intellectual sources comprehensively. This paper aims to analyze G.H.A Juynboll’s views in dealing with prophetic tradition. This was investigated from his thoughtful and broad understanding of its principle and underlying purpose. The essential understanding of the principle of prophetic tradition was analytically discussed in his magnum opus such as; Muslim Tradition: Studies in Chronology, Provenance and Authorship of Early Hadith , Studies on the Origin and Uses of Islamic Hadith, and (Re)Appraisal of Some Technical Terms in Hadith Science. The finding shows that G.H.A Juynboll’s discussion on prophetic tradition emphasized on irrelevance to contemporary practice and modern context of Islam. It set forth important framework and methodology towards reforming prophetic tradition, but have been critically by most of prominet Muslim scholars due to contradiction between his methodology and Islamic principle methodology.